Linkage of the CF foundation patient registry with the pediatric health information system database. Issue 6 (18th March 2019) - Cogen, Jonathan D.; Hall, Matt; Loeffler, Deena R.; Gove, Nancy; Onchiri, Frankline; Sawicki, Gregory S.; Fink, Aliza K.
Abstract: Introduction: The Cystic Fibrosis Foundation Patient Registry (CFFPR) contains clinical and demographic data from ∼85% of US cystic fibrosis (CF) patients across 120 care centers, but lacks robust inpatient hospitalization data. In contrast, the Pediatric Health Information System (PHIS) database includes inpatient clinical and resource utilization data from 49 US children's hospitals. The creation of a linked CFFPR‐PHIS dataset can uniquely address questions related to in‐hospital pediatric CF treatment and management. We assessed the feasibility of linking the CFFPR and PHIS databases and determined if successfully linked CF patients were generalizable to unlinked patients. Methods: CF patients ≤21 years were eligible for linkage. The CFFPR and PHIS databases were linked at the patient level using indirect identifiers in a stepwise, deterministic, linkage approach. A validation cohort was created using a subset of patients to determine linkage accuracy. Clinical and demographic characteristics between linked and unlinked patients were compared to determine generalizability of the linked cohort. Results: Of the 11 735 CF patients eligible for linkage from January 1st, 2005 through December 31st, 2016, 10 660 (91%) were successfully linked. Results of our single center validation cohort illustrated 100% accuracy. When compared to unlinked CF patients, fewer linked patients were born before 1990, more were Hispanic, and more were from West‐affiliated PHIS hospitals. Otherwise, no clinically meaningful differences were seen between linked and unlinked CF patients. Conclusions: We demonstrated successful linkage of the CFFPR and PHIS databases, and created a large generalizable pediatric CF cohort for use in CF‐related research.